Permeation of Active Ingredient in Pesticide Formulations Through Single-Use and Reusable Chemical-Resistant Gloves - Shaw, Anugrah; Coleone, Ana Carla [UNESP]; Machado-Neto, Joaquim [UNESP]; Shiels, B.; Lehtonen, K. (Astm International, 2016)
In the United States, the Environmental Protection Agency's Chemical Resistance Category Selection Chart for Gloves is used to assign glove requirements on product labels for pesticide applicators. These requirements, based on the breakthrough time of solvents, continue to be used as the basis for assigning gloves even though they were intended as a starting point in the 1980s. Recent revisions to the EPA's Label Review Manual state that any waterproof glove can be used for dry and water-based formulations. On the other hand, barrier laminate and >= 15-mil-thick Viton (R) (Aero Rubber Co., Inc., Tinley Park, IL) gloves are the only two glove materials for formulations that contain >40 % aromatic petroleum distillates or halogenated hydrocarbon solvents. Of these, barrier laminate has limitations in regard to fit and dexterity, and Viton gloves are very expensive. A survey of operators found that they often wear nitrile and neoprene gloves, including single-use gloves that have not been evaluated. The purpose of the study was to measure cumulative permeation through chemical-resistant gloves to support the development of an international performance standard for gloves and to initiate discussion in the United States on the need to simplify glove requirements for pesticide operators. The study was conducted with a recently developed method to evaluate the permeation of active ingredients through five single-use and seven reusable chemical-resistant gloves. Permeation tests were conducted with dilute formulations and concentrates of seven pesticide formulations. The duration time of 15 min was used for tests conducted with concentrates because operators are required to remove the gloves immediately in the case of an accidental spill. Data show low levels of permeation of active ingredients in some formulations with no carrier solvent. Results also indicate that gloves such as those made of reusable nitrite and neoprene can provide good protection against formulations that contain >40 % aromatic petroleum distillates.
Keywords: permeation; pesticides; glove requirements